Pengaruh Leverage, Likuiditas dan Profitabilitas terhadap Nilai Perusahaan pada Airlines Company Listed IDX 2011-2020 - Nur Laili Fitriana; Purwohandoko Purwohandoko (Jurnal Ilmu Manajemen, 2022)
This study aims to analyse the influence of leverage, liquidity, and profitability on a firm value on the airline's company listed IDX 2011-2020. The firm value is the fair market value of the share price and is a benchmark of the company's management success. The PBV ratio states firm value as a dependent variable in this study. This research is causal research with quantitative and secondary data types. This study used a multiple linear regression method that SPSS measured as its analytical tool with the population in the form of all airlines listed on the IDX. The sampling method is purposive, resulting in 3 sample companies with codes GIAA, IATA, and CMPP. The results show that leverage proxied by DER has a significant effect on firm value. At the same time, there is no significant effect of liquidity proxied by CR and profitability proxied by ROE on firm value. Based on the result of this study, a company should determine their equity structure, use current assets well, and choose reinvestment than distributing cash dividends as an effort to improve its firm value.